Halogen anion substituted type rare earth fluoride nano scintillator with high luminous efficiency and application of halogen anion substituted type rare earth fluoride nano scintillator

By replacing the F-ion of NaYF4:Tb nanoparticles by halogen anions, the problem of low luminescence intensity and afterglow performance of traditional nanoscintballs under X-ray excitation is solved, and the effect of significantly improving the luminescence intensity and afterglow intensity is achieved, and optical stability is maintained.

CN119736088APending Publication Date: 2025-04-01FOURTH MILITARY MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411986096.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The low luminous intensity and afterglow performance of traditional rare earth fluoride nanoscintifiers under X-ray excitation limits their applications in fields such as high-sensitivity X-ray detectors and high-resolution X-ray imaging.

Method used

By replacing the F-ions in NaYF4:Tb nanoparticles with halogen anions such as Cl, Br or I, it causes lattice mismatch, promotes the formation of Frank defects and the formation of shallow trap energy levels, thereby regulating the luminous intensity and afterglow performance.

Benefits of technology

The luminescence intensity and afterglow intensity under X-ray excitation were significantly improved. The luminescence intensity of NaYF3.2Br0.8:10%Tb was increased by more than 3 times, and the afterglow intensity was increased by more than 4.2 times, and long-term optical stability was maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736088A_ABST
    Figure CN119736088A_ABST
Patent Text Reader

Abstract

The invention discloses a halogen anion substituted rare earth fluoride nano scintillator for improving X-ray excitation luminescence intensity and afterglow intensity and a preparation method and application thereof, and belongs to the technical field of biological nano materials. The chemical formula of the nano scintillator is NaAF (4-n) Xn: m% Tb, A represents Y, Er, Gd, Lu or Yb, X represents Cl, Br or I, n is larger than or equal to 0.1 and smaller than or equal to 1.6, and m is larger than or equal to 5 and smaller than or equal to 20. Part of F <-> ions are replaced by halogen anions (Cl <->, Br <-> and I <->), and the X-ray excitation luminescence intensity and afterglow intensity can be remarkably improved. A transmission electron microscope (TEM) shows that the prepared nanoparticles are spherically distributed in morphology, uniform in size and good in dispersity, and the particle size is intensively distributed at 25nm. After continuous six times of cyclic irradiation by X-rays (80kV, 0.7 mA), long-term optical stability can still be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biological nanomaterials, and in particular, relates to a halogen anion substituted rare earth fluoride nano-scintillator capable of improving X-ray excitation luminescence intensity and afterglow intensity, and a preparation method and application thereof. Background Art

[0002] Scintillators can convert high-energy X-rays and gamma rays into ultraviolet (UV), visible light (Visible) or near-infrared (NIR) photons, and are widely used in X-ray imaging in medical diagnosis, fluorescent probes for tumor labeling, X-ray flat panel detectors, non-destructive industrial flaw detection and safety detection. Traditional commercial bulk scintillators, such as ZnGa2O4:Cr, CdTe, Gd2(WO4)3 and CsPbBr3, have high light yield and excellent X-ray response. However, commercial bulk scintillators not only require complex preparation processes and expensive experimental equipment, but also show poor device processability and heavy metal toxicity, which limits their further application in optical devices and biomedical fields. Rare earth fluoride nanoscintillators prepared by solvent thermal chemical synthesis method have many advantages such as low toxicity, low manufacturing cost, convenient device processing, and tunable emission wavelength. In addition, they also show X-ray excited long afterglow luminescence, which further expands their application range. In recent years, they have been widely studied in the field of X-ray luminescence.

[0003] Although traditional rare earth fluoride nanoscintillators exhibit excellent down-conversion luminescence characteristics, excessive surface defects are generated during the synthesis process, and the luminescence intensity and afterglow performance under X-ray excitation still need to be improved. For example, NaYF4, as a typical rare earth fluoride matrix material, has greatly improved luminescence performance compared to traditional commercial scintillators, but the currently synthesized nanoparticles are affected by surface defects, resulting in low luminescence intensity and afterglow intensity under X-ray excitation, which limits its application in high-sensitivity X-ray detectors, high-resolution X-ray imaging and other fields. Therefore, it is of great significance to develop rare earth fluoride matrix materials with higher X-ray excitation luminescence and afterglow performance. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a halogen anion substituted rare earth fluoride nanoscintillator that improves the X-ray excitation luminescence intensity and afterglow intensity, and a preparation method and application thereof.

[0005] In order to achieve the above technical objectives, the inventors creatively proposed a halogen anion substitution strategy to replace the F in NaYF4:Tb nanoparticles. -The ions are replaced by other halogen anions (Cl, Br, I) respectively. The replacement of halogen anions with different ionic radii and electronegativity causes lattice mismatch, promotes the generation of Frank defects in the matrix under X-ray irradiation, is beneficial to the formation of shallow trap energy levels, and can effectively regulate the luminescence intensity and afterglow performance.

[0006] Specifically, the object of the present invention is achieved through the following technical solution: a halogen anion substituted rare earth fluoride nanoscintillator, the chemical formula of the nanoscintillator is NaAF(4-n)Xn:m%Tb, wherein A represents Y, Er, Gd, Lu or Yb, X represents Cl, Br or I, 0.1≤n≤1.6, 5≤m≤20 (preferably, 0.6≤n≤1, 8≤m≤12.). - Br - ,I - ) replace part F - ions, which can significantly improve the X-ray excitation luminescence intensity and afterglow intensity. Transmission electron microscopy (TEM) shows that the prepared nanoparticles are spherical in shape, uniform in size and well dispersed, with the particle size concentrated at 25nm. After 6 consecutive cycles of X-ray (80kV, 0.7mA) irradiation, they can still maintain long-term optical stability. Compared with the unsubstituted NaYF4:10%Tb material, the most preferred luminescent material NaYF 3.2 Br 0.8 : The luminous intensity of 10% Tb can be increased by more than 3 times, and the afterglow intensity can be increased by more than 4.2 times.

[0007] A preparation method of the above-mentioned halogen anion substituted rare earth fluoride nano-scintillator, the method comprising the following steps: ACl3, TbCl3, oleic acid and 1-octadecene are mixed, heated to 140-160°C under the protection of an inert gas until a clear and transparent solution is formed, then a methanol solution containing NH4F, NH4X and NaOH is added, and the methanol is stirred to remove the methanol, and then the mixed solution is further heated to 280-320°C at a heating rate of 8-12°C / min, and the mixture is kept warm for reaction for 1-2h under the protection of an inert gas, and finally cooled to room temperature, and the cooled reaction product is centrifuged at high speed, and the precipitate is separated and washed to obtain halogen anion substituted rare earth fluoride nano-scintillator NaAF(4-n)Xn:m%Tb nano-particles.

[0008] Further preferably, in the method for preparing the halogen anion substituted rare earth fluoride nano-scintillator as described above, the volume ratio of oleic acid to 1-octadecene is 1:(1.5-3).

[0009] Further preferably, in the method for preparing the halogen anion substituted rare earth fluoride nanoscintillator as described above, the speed of high-speed centrifugation of the obtained reaction product is 8000-12000 rpm.

[0010] Further preferably, in the method for preparing the halogen anion substituted rare earth fluoride nano-scintillator as described above, the obtained precipitate is washed 1 to 5 times with a mixed solution of ethanol / cyclohexane in a volume ratio of 2:1.

[0011] Further preferably, in the method for preparing the halogen anion substituted rare earth fluoride nano-scintillator as described above, the obtained NaAF(4-n)Xn:m%Tb nano-particles are dispersed in cyclohexane for storage.

[0012] The prepared NaAF(4-n)Xn:m%Tb nanoparticles of the present invention produce stronger green fluorescence emission under the excitation of X-rays (80kV, 0.7mA). After 6 consecutive cycles of X-ray irradiation, the luminescence intensity of X-ray excitation is almost unchanged, proving that it has excellent optical stability. Therefore, another object of the present invention is to provide a new use of a product, namely, the use of the above-mentioned halogen anion substituted rare earth fluoride nanoscintillator in the preparation of persistent luminescent imaging materials, and the use of the above-mentioned halogen anion substituted rare earth fluoride nanoscintillator in the preparation of X-ray detectors, X-ray imaging equipment or fluorescent probes of biological markers or X-ray excited photoelectric devices.

[0013] Compared with the prior art, the halogen anion substituted rare earth fluoride nano-scintillator nanoparticles prepared by the present invention have the following advantages and advancements:

[0014] (1) NaAF(4-n)Xn:m%Tb nanoparticles have controllable morphology and good crystal structure stability: Despite the substitution of halogen ions, the material still maintains a hexagonal crystal structure consistent with NaYF4. In addition, the morphology and particle size of the synthesized nanoparticles remain basically unchanged, and they are all monodisperse spherical, which ensures the stability of the material phase structure during preparation and practical application.

[0015] (2) X-ray induced luminescence intensity is significantly improved: halogen anions (Cl, Br, I) replace F - ions, due to the interaction of other halogen ions with F - The differences in atomic radius and electronegativity of ions change the crystal field coordination environment of the material. This change can effectively enhance the 4f-4f transition probability of rare earth doped ions, thereby improving the luminescence intensity under X-ray excitation. Compared with the unsubstituted NaYF4:Tb material, the optimal luminescent material NaYF in the present invention is 3.2 Br 0.8 : The luminescence intensity of 10% Tb can be increased by more than 3 times.

[0016] (3) The afterglow intensity is significantly enhanced: The substitution of other halogen ions is conducive to the formation of Frank defects in the matrix. During the X-ray excitation process, more electrons and holes can be effectively captured and stored in the traps. When the excitation stops, the captured carriers are slowly released and recombine with the luminescence center, thereby significantly enhancing the afterglow intensity and afterglow time. The optimal luminescent material NaYF in the present invention is 3.2 Br 0.8 : The afterglow intensity of 10% Tb can be increased by more than 4.2 times.

[0017] (4) The NaAF(4-n)Xn:m%Tb nanoparticle luminescent material of the present invention can be applied to X-ray detectors, X-ray imaging equipment (such as medical X-ray imaging, industrial non-destructive testing imaging, etc.), fluorescent probes for tumor marking, and X-ray excited optoelectronic devices and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : TEM images of nanoparticles prepared in Example 1, where ad are NaYF4:10%Tb, NaYF 3.2 Cl 0.8 :10%Tb、NaYF 3.2 Br 0.8 :10%Tb、NaYF 3.2 I 0.8 :10%Tb.

[0019] Figure 2 : NaYF4:10%Tb and NaYF prepared in Example 1 3.2 X 0.8 The XRD patterns of 10% Tb (wherein X represents Cl, Br or I) nanoparticles all match the standard diffraction peaks of hexagonal β-NaYF4 (JCPDS No.16-0334).

[0020] Figure 3 :Different I - NaYF with doping concentrations (x = 0, 5, 10, 20, 30 and 40 mol%) (4-4x) I 4x : X-ray excitation emission spectrum of 10% Tb.

[0021] Figure 4 : After 5 minutes of X-ray excitation, NaYF (4-4x) I 4x : Afterglow emission spectra of 10% Tb (x = 0, 5, 10, 20, 30 and 40 mol%).

[0022] Figure 5:NaYF4:10%Tb and NaYF 3.2 X 0.8 : X-ray excitation emission spectrum of 10% Tb (where X represents Cl, Br or I) nanoparticles.

[0023] Figure 6 :After 5min of X-ray excitation, NaYF4:10%Tb and NaYF 3.2 X 0.8 : Afterglow emission spectrum of 10% Tb (where X represents Cl, Br or I) nanoparticles.

[0024] Figure 7 :After 5min of X-ray excitation, NaYF4:10%Tb and NaYF 3.2 X 0.8 : Afterglow decay curve of 10% Tb (where X represents Cl, Br or I) nanoparticles.

[0025] Figure 8 :NaYF4:10%Tb and NaYF 3.2 X 0.8 The luminescence stability of 10% Tb (wherein X represents Cl, Br or I) nanoparticles was tested under 6 consecutive cycles of X-ray (80 kV, 0.7 mA) irradiation. DETAILED DESCRIPTION

[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in combination with specific implementation methods, but the present invention is not limited to this. The specific experimental process is as follows:

[0027] Example 1

[0028] (1) Preparation of NaYF4:10%Tb Nanoparticles

[0029] First, a mixed solution of YCl3 (0.9mmol), TbCl3 (0.1mmol), oleic acid OA (15mL) and 1-octadecene ODE (25mL) was added to a 100mL round-bottom flask. It was heated to 140-160°C under argon protection until a clear and transparent solution was formed, and then cooled to 50°C. Next, 10mL of a methanol solution containing NH4F (4mmol) and NaOH (2.5mmol) was added to the mixture and stirred for 30min to remove methanol. Then, the solution was further heated to 290-320°C at a heating rate of 10°C / min, heated for 1-2h under an argon atmosphere, and cooled to room temperature. The cooled solution was centrifuged at 10000rpm to obtain a precipitated product, and the precipitate was washed 3 times with an ethanol / cyclohexane mixture (2:1, v / v), and finally dispersed in 10mL of cyclohexane.

[0030] (2) NaYF(4-n)X after halogen anion substitution n Preparation of 10% Tb nanoparticles

[0031] A mixed solution of YCl3 (0.9 mmol), TbCl3 (0.1 mmol), oleic acid OA (15 mL) and 1-octadecene ODE (25 mL) was added to a 100 mL round-bottom flask. It was heated to 140-160 ° C under argon protection until a clear and transparent solution was formed, and then 10 mL of a methanol solution containing NH4F (4-n mmol), NH4X (X represents Cl, Br or I, n mmol, 0≤n≤1.6) and NaOH (2.5 mmol) was added to the mixture and stirred for 30 min to remove methanol. Then, the solution was further heated to 280-320 ° C at a heating rate of 10 ° C / min, heated for 1-2 h under an argon atmosphere, and cooled to room temperature. The cooled solution was centrifuged at 10000 rpm to obtain a precipitated product, and the precipitate was washed 3 times with an ethanol / cyclohexane mixture (2:1, v / v), and finally dispersed in 10 mL of cyclohexane. NaErF can be obtained by replacing the rare earth chloride YCl3 with ErCl3, GdCl3, LuCl3 or YbCl3 3.2 X 0.8 :10%Tb、 FWf 3.2 X 0.8 :10%Tb、NaLuF 3.2 X 0.8 :10%Tb、NaYbF 3.2 X 0.8 :10%Tb nanoparticles.

[0032] In this example, NaYF4:10%Tb and NaYF were prepared by solvothermal method. 3.2 X 0.8 : Transmission electron microscopy (TEM) images of 10% Tb (where X represents Cl, Br or I) nanoparticles, such as Figure 1 The XRD pattern of the synthesized nanoparticles is shown in Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the nanoparticles after halogen anion substitution are spherical, with good uniformity and dispersion, and a particle size of about 25nm. The crystal structure is a typical hexagonal β phase, and the XRD diffraction pattern is clear, which proves its high crystallinity and ensures the stability of the phase structure of the material during preparation and practical application.

[0033] A series of I - Doped NaYF4 nanoparticles, recorded NaYF (4-4x) I 4x : The emission spectra and afterglow spectra of 10% Tb (x = 0, 5, 10, 20, 30 and 40 mol%) nanoparticles under X-ray excitation (80 kV, 0.7 mA) were observed. The luminescence intensity of the nanoparticles increased with I - The trend of doping concentration change. Figure 3 As shown, the nanoparticles showed Tb under X-ray excitation. 3+The characteristic emission peaks are 488, 545, 586 and 625nm, respectively, and the strongest emission peak is in the 545nm green light range. - With the increase of doping ratio, the displacement of emission peak has not changed, but the overall luminescence intensity shows a trend of increasing first and then decreasing, reaching the optimum when the doping amount is 20%. The reason is that I - The ionic radius of F - The ions are large, and doping will cause the lattice volume to expand, destroy the symmetry of the local site, and increase the luminescence center Tb 3+ ions, resulting in enhanced luminescence. However, further increasing the doping level will make the luminescence center Tb 3+ The energy transfer between them produces harmful cross relaxation, resulting in self-quenching effect and reduced luminescence intensity.

[0034] In order to explore I - The effect of doping concentration on afterglow intensity, such as Figure 4 As shown, the X-ray excitation was turned off after 5 minutes, and different I - The afterglow spectrum of the doping concentration was found to be basically consistent with the change of the luminous intensity, and the afterglow intensity reached the highest when the doping amount was 20%. This is due to the appropriate concentration of I - Doping is conducive to forming a suitable trap depth and concentration in the main matrix, resulting in an increase in the afterglow intensity. Therefore, all subsequent halogen ion doping is prepared according to the above-mentioned optimal doping concentration of 20%.

[0035] By exploring the substitution of different halide ions for F - The influence of ions on the luminescence properties, such as Figure 5 As shown, NaYF 3.2 X 0.8 The X-ray excitation emission spectrum of 10% Tb (where X represents Cl, Br or I) nanoparticles shows that Br - After ion substitution, the luminescence intensity is three times that of unsubstituted. Figure 6 and Figure 7 As shown, Br - Ion partially replaces F - The afterglow intensity and decay time of the ions are significantly improved, and the afterglow intensity is 4.2 times that of the unsubstituted state, and the luminescence performance is greatly improved. Figure 8 As shown, after 6 consecutive cycles of X-ray (80 kV, 0.7 mA) irradiation, the luminescence intensity excited by X-rays hardly changed, proving that it has excellent optical stability.

Claims

1. A halogen anion substituted rare earth fluoride nanoscintillator, characterized in that: The chemical formula of the nano scintillator is NaAF(4-n)Xn:m%Tb, wherein A=Y, Er, Gd, Lu or Yb, X=Cl, Br or I, 0.1≤n≤1.6, 5≤m≤20.

2. The halogen anion substituted rare earth fluoride nanoscintillator according to claim 1, characterized in that: 0.6≤n≤1,8≤m≤12.

3. The halogen anion substituted rare earth fluoride nanoscintillator according to claim 1, characterized in that: The chemical formula of the nano scintillator is NaYF 3.2 Br 0.8 :10%Tb.

4. A method for preparing the halogen anion substituted rare earth fluoride nanoscintillator according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing ACl3, TbCl3, oleic acid and 1-octadecene, heating to 140-160°C under the protection of an inert gas until a clear and transparent solution is formed, then adding a methanol solution containing NH4F, NH4X and NaOH, stirring to remove the methanol, then further heating the mixed solution to 280-320°C at a heating rate of 8-12°C / min, keeping the mixture warm for 1-2h under the protection of an inert gas, and finally cooling to room temperature, centrifuging the cooled reaction product at high speed, separating the precipitate and washing it to obtain halogen anion substituted rare earth fluoride nano-scintillator NaAF(4-n)Xn:m%Tb nano-particles.

5. The method for preparing the halogen anion substituted rare earth fluoride nanoscintillator according to claim 4, characterized in that: The volume ratio of oleic acid to 1-octadecene is 1:(1.5-3).

6. The method for preparing the halogen anion substituted rare earth fluoride nanoscintillator according to claim 4, characterized in that: The speed of high-speed centrifugation of the reaction product is 8000-12000 rpm.

7. The method for preparing the halogen anion substituted rare earth fluoride nanoscintillator according to claim 4, characterized in that: The precipitate is washed 1 to 5 times with an ethanol / cyclohexane mixture in a volume ratio of 2:

1.

8. The method for preparing the halogen anion substituted rare earth fluoride nanoscintillator according to claim 4, characterized in that: The NaAF(4-n)Xn:m%Tb nanoparticles are dispersed in cyclohexane and stored.

9. Use of the halogen anion substituted rare earth fluoride nanoscintillator according to any one of claims 1 to 3 in the preparation of persistent luminescent imaging materials.

10. Use of the halogen anion substituted rare earth fluoride nanoscintillator according to any one of claims 1 to 3 in the preparation of X-ray detectors, X-ray imaging equipment, or fluorescent probes for biological markers or X-ray excited photoelectric devices.